2020
DOI: 10.29328/journal.jro.1001033
|View full text |Cite
|
Sign up to set email alerts
|

Role of HRCT Thorax in pre-operative assessment of RT-PCR COVID-19 negative oral cancer patients

Abstract: Background: Oral cancer accounts for 30% of all types of cancer in India. Surgery is the mainstay of treatment but due to the recent outbreak of COVID-19, there is a partial or complete disruption of health services in the country. The initial delay in the treatment was due to cancellations of planned surgeries as per government regulations and reduction in public transportation. In the latter half of the initial relaxation of the lockdown, we formulated our institutional protocol for the surgical treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…The findings in our study were substantiated by study conducted by Ai Tao, et al, [7] where patients with negative RT-PCR tests, more than 70% had typical CT manifestations due to the overlap of CT imaging features between COVID-19 and other viral pneumonia and false-positive cases of COVID-19 can be identified with chest CT. manifestations, and dynamic CT follow-up. The findings of our study are also consistent with study conducted by Ganta R, et al, [8] which showed that 60 patients showed minor abnormalities on HRCT thorax. The purpose of this study was to ensure safety of Front liners which was done by excluding false negative cases by subjecting them to Ct scan thorax which was considered more accurate and sensitive than viral nucleic acid assay and the findings were also proven by FANG, et al, compare the sensitivity of chest CT and viral nucleic acid assay at initial patient presentation and found 51 patients with chest CT and RT-PCR assay performed within 3 days, the sensitivity of CT for COVID-19 infection was 98% compared to RT-PCR sensitivity of 71% (p<.001).…”
Section: Methodssupporting
confidence: 93%
“…The findings in our study were substantiated by study conducted by Ai Tao, et al, [7] where patients with negative RT-PCR tests, more than 70% had typical CT manifestations due to the overlap of CT imaging features between COVID-19 and other viral pneumonia and false-positive cases of COVID-19 can be identified with chest CT. manifestations, and dynamic CT follow-up. The findings of our study are also consistent with study conducted by Ganta R, et al, [8] which showed that 60 patients showed minor abnormalities on HRCT thorax. The purpose of this study was to ensure safety of Front liners which was done by excluding false negative cases by subjecting them to Ct scan thorax which was considered more accurate and sensitive than viral nucleic acid assay and the findings were also proven by FANG, et al, compare the sensitivity of chest CT and viral nucleic acid assay at initial patient presentation and found 51 patients with chest CT and RT-PCR assay performed within 3 days, the sensitivity of CT for COVID-19 infection was 98% compared to RT-PCR sensitivity of 71% (p<.001).…”
Section: Methodssupporting
confidence: 93%